Preventing mpox at its source: Using food safety and One Health strategies to address bushmeat practices - Lam, Steven; Masudi, Sherril P.; Ha Thi Thanh Nguyen; Grace, Delia (Springer, 2024)
A key step in preventing mpox at its source is to address the handling and consumption of bushmeat from potential animal reservoirs. Changes to these practices must consider social, economic, and environmental factors, making a collaborative One Health approach essential. We propose a pilot intervention as a way forward.